2021
DOI: 10.1021/acs.jpcb.1c05082
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of Dimerization-Induced Intersystem Crossing: At the Origins of Spin–Orbit Coupling Selection Rules

Abstract: Singlet-Triplet interconversions and transitions (intersystem crossing, ISC) in organic molecules are at the basis of many important processes in cutting-edge photonic applications (Organic Light Emitting Devices, photodynamic therapy…). Selection rules for these transitions are mainly governed by the Spin-Orbit Coupling (SOC) phenomenon. Although the latter relies on complex relativistic phenomena, theoreticians have, with time, developed increasingly sophisticated and efficient approaches to gain access to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…As is expected, the energetic cost for twisting the PDI gradually increases with φ and reaches up to 10.4 kcal mol –1 for φ = 40 0 (see S 0 evolution from Figure ). Here, we point out that the dynamics at finite temperature may yield such twisted PDI structures and thereby can modulate the photophysics and related energetics as discussed elsewhere . The S 1 and T n energies, SOC, and λ S 1 – T n between S 1 and T n are calculated to understand the effect of the core-twist on these key energetic parameters that govern the ISC rate.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…As is expected, the energetic cost for twisting the PDI gradually increases with φ and reaches up to 10.4 kcal mol –1 for φ = 40 0 (see S 0 evolution from Figure ). Here, we point out that the dynamics at finite temperature may yield such twisted PDI structures and thereby can modulate the photophysics and related energetics as discussed elsewhere . The S 1 and T n energies, SOC, and λ S 1 – T n between S 1 and T n are calculated to understand the effect of the core-twist on these key energetic parameters that govern the ISC rate.…”
Section: Resultssupporting
confidence: 76%
“…Eco-friendly, heavy-atom-free small organic molecules are promising candidates because of their easily tunable physiochemical properties and flexibility. However, negligibly small SOC in these systems leads to inefficient ISC, restricting their practical use as triplet photosensitizers. Conventionally, a large SOC is achieved by an internal heavy-atom effect. , In addition, strategies such as substitutional doping with light hetero-elements (for example, “N”), defects, dielectric screening, and also introducing geometrical strains were shown to improve the ISC/RISC rates. Significantly enhanced ISC was reported for heavy-atom-free perylenediimide (PDI) bay-substituted with electron-donor units. , A considerable ISC rate was also reported for a geometrically twisted phenanthrene-fused PDI, whereas the corresponding planar analogue produced a negligibly small ISC rate . PDI functionalized with anthryl and carbazole at the bay positions exhibits long lived triplet with substantially high triplet quantum yield (Φ T ) .…”
Section: Introductionmentioning
confidence: 99%
“…This dimerization induced ISC has been rationalized in the past for a variety of compounds, 36,37 including in particular bodipy derivatives, 38–40 and already observed and explained by some of us in a previous report on BTI dimers. 41 Here again, TD-DFT calculations revealed that a strong dynamic excitonic coupling between the two TCI subunits in the TCI 2 dimer result in enhanced spin–orbit coupling constant between the excited singlet and lower triplet states (see Fig. 6b and Fig.…”
Section: Resultsmentioning
confidence: 70%
“…These results suggest that radiative and nonradiative decays from the lowest triplet exciton states of molecular aggregates, intimately related to the nature and symmetry of the lowest energy state, may be modulated by the intermolecular organization, a concept that could be exploited for systems displaying dimerization-induced triplet state populations [57].…”
Section: Modulation Of Triplet Exciton-state Energies and Characters ...mentioning
confidence: 96%
“…Thus, triplet formation by charge recombination can be a detrimental, unwanted side effect but can also be exploited as a useful triplet-generation method, for instance in photocatalysis and photodynamic therapy [54,55]. Examples are, among others, triplet-state generation in molecular dyads [56] and molecular dimers in which dimerization-induced triplet population has been invoked [57].…”
Section: Introductionmentioning
confidence: 99%